2016
DOI: 10.1039/c5ee02806j
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of organic active materials in carbon nanotubes for application to high-electrochemical-performance sodium batteries

Abstract: A PTMA-impregnated CNT electrode achieves the enhancement of discharge capacity, cycleability and rate capability of sodium batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(113 citation statements)
references
References 33 publications
1
112
0
Order By: Relevance
“…2017, 7, 1601792 www.advenergymat.de www.advancedsciencenews.com insertion/extraction at high voltages, but also n-doping and de n-doping reactions with Na-ion insertion and extraction at relative low voltages. [18] They adopted a facile method to encapsulate PTMA into carbon nanotubes with diameter of about 100 to 300 nm. 54, Figure 10) [72] was initially reported as a possible cathode for SIBs with the electrolyte of 1 m NaClO 4 / (ethylene carbonate) EC-(dimethyl carbonate) DMC.…”
Section: Organic Radical Compoundsmentioning
confidence: 99%
“…2017, 7, 1601792 www.advenergymat.de www.advancedsciencenews.com insertion/extraction at high voltages, but also n-doping and de n-doping reactions with Na-ion insertion and extraction at relative low voltages. [18] They adopted a facile method to encapsulate PTMA into carbon nanotubes with diameter of about 100 to 300 nm. 54, Figure 10) [72] was initially reported as a possible cathode for SIBs with the electrolyte of 1 m NaClO 4 / (ethylene carbonate) EC-(dimethyl carbonate) DMC.…”
Section: Organic Radical Compoundsmentioning
confidence: 99%
“…63 ) and poly(2,2,6,6‐tetra methylpiperidinyloxy‐4‐vinylmethacrylate) (PTMA, No. 64 ) were investigated on OSIBs in the past decades . Their structural units all contain nitroxyl radical 2,2,6,6‐tetramethyl‐1‐piperidinyloxy (TEMPO).…”
Section: Research Progress Of Organic Electrode Materialsmentioning
confidence: 99%
“…Previously, researchers used SWNT FETs to investigate charge transfer between fullerene and SWNTs. For example, Li et al showed that carbon peapods display a photo‐induced electron transfer from encapsulated C 60 to SWNTs, exhibiting p ‐type characteristic on illumination . Park et al reported thermally deposited C 60 on SWNTs resulting in ambipolar SWNT FETs and a left shift of the threshold voltage, which became stronger with the increasing thickness of the deposited C 60 .…”
Section: Resultsmentioning
confidence: 99%